ANALISIS FAKTOR-FAKTOR PENCEGAHAN HIV/AIDS PADA MAHASISWA KEPERAWATAN DENGAN PENDEKATAN TEORI HEALTH BELIEF MODEL - Febriyanti, Erna (Jurnal Kesehatan, 2021)
ABSTRACT Human Immunodeficiency Virus (HIV) is still a major public health problem in various countries including Indonesia. Students are a group of adolescents of productive age who are at this age vulnerable to HIV / AIDS transmission. Adolescence is the age of the majority of students who are considered vulnerable to infection because of their lack of knowledge about the dangers of HIV / AIDS. The purpose of this study was to determine the factors associated with HIV / AIDS prevention in nursing students. The method in this research is quantitative with a cross sectional approach. The study population was nursing students at Citra Bangsa University and STIKes Maranatha Kupang. The research sample was nursing students who were taken by purposive sampling technique with a sample size of 100 respondents, then analyzed using the Chi Square test. The results showed that perceptions of perceived vulnerability, perceptions of perceived seriousness, perceptions of perceived benefits, perceptions of perceived barriers, perceptions of cues to action, self-efficacy have a significant relationship with HIV / AIDS prevention in Citra Bangsa University and STIKes students. Maranatha Kupang. The results of this study are useful for the students concerned to maintain and improve their behavior to prevent HIV / AIDS and other sexually transmitted diseases. . Keywords: Factors, Behavior, Prevention, HIV / AIDS.